Aging Faces and Aging Perceivers: Young and Older Adults are Less Sensitive to Deviations from Normality in Older Than in Young Adult Faces. (August 2013) - Short, Lindsey A; Mondloch, Catherine J
Past studies examining the other-age effect, the phenomenon in which own-age faces are recognized more accurately than other-age faces, are limited in number and report inconsistent results. Here we examine whether the perceptual system is preferentially tuned to differences among young adult faces. In experiment 1 young (18–25 years) and older adult (63–87 years) participants were shown young and older face pairs in which one member of each pair was undistorted and the other had compressed or expanded features. Participants indicated which member of each pair was more normal and which was more expanded. Both age groups were more accurate when tested with young compared with older faces—but only when judging normality. In experiment 2 we tested a separate group of young adults on the same two tasks but with upright and inverted face pairs to examine the differential pattern of results between the normality and discrimination tasks. Inversion impaired performance on the normality task but not the discrimination task and eliminated the young adult advantage in the normality task. Collectively, these results suggest that the face processing system is optimized for young adult faces and that abundant experience with older faces later in life does not reverse this perceptual tuning.